(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is devoted to the issues of learning foreign languages, especially English as a second language. During the process of learning students should learn vocabulary units. In this article we try to identify the main points and give the best solutions.